2021
DOI: 10.3390/ijms22062982
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity Kinase DYRK3 Promotes Aggressiveness of Glioblastoma by Altering Mitochondrial Morphology and Function

Abstract: Glioblastoma multiforme (GBM) is a malignant primary brain tumor with poor patient prognosis. Although the standard treatment of GBM is surgery followed by chemotherapy and radiotherapy, often a small portion of surviving tumor cells acquire therapeutic resistance and become more aggressive. Recently, altered kinase expression and activity have been shown to determine metabolic flux in tumor cells and metabolic reprogramming has emerged as a tumor progression regulatory mechanism. Here we investigated novel ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…14 DYRK3 has recently been found to reduce mitochondrial oxidative phosphorylation and increase glycolysis by activating Drp-1 (dynamic-related protein 1)–mediated mitochondrial fission. 15 In this study, we found that the transcriptional level of DYRK1B, rather than other members of the DYRK family, was distinctively upregulated in myocardium of patients who had dilated cardiopathy (DCM), ischemic cardiomyopathy, and hypertrophic cardiomyopathy (HCM) compared with those of patients with nonfailing myocardium, suggesting the indispensable role of DYRK1B in the progression of HF. In addition, it was recently reported that DYRK1B mutation is directly linked with human genetic diseases, its gain-of-function mutation at position 102 precisely predicts early-onset coronary artery disease, central obesity, hypertension, and diabetes, highlighting the important role of DYRK1B in energy metabolism and heart diseases.…”
mentioning
confidence: 75%
“…14 DYRK3 has recently been found to reduce mitochondrial oxidative phosphorylation and increase glycolysis by activating Drp-1 (dynamic-related protein 1)–mediated mitochondrial fission. 15 In this study, we found that the transcriptional level of DYRK1B, rather than other members of the DYRK family, was distinctively upregulated in myocardium of patients who had dilated cardiopathy (DCM), ischemic cardiomyopathy, and hypertrophic cardiomyopathy (HCM) compared with those of patients with nonfailing myocardium, suggesting the indispensable role of DYRK1B in the progression of HF. In addition, it was recently reported that DYRK1B mutation is directly linked with human genetic diseases, its gain-of-function mutation at position 102 precisely predicts early-onset coronary artery disease, central obesity, hypertension, and diabetes, highlighting the important role of DYRK1B in energy metabolism and heart diseases.…”
mentioning
confidence: 75%
“…DYRK3 promotes hepatocellular carcinoma [ 121 ] and glioblastoma [ 122 ]. DYRK3 is required for influenza virus replication [ 123 ].…”
Section: Dyrks and Human Diseasementioning
confidence: 99%
“…DYRK2 is involved in various ways in cancer development (reviews: [119,120]). DYRK3 promotes hepatocellular carcinoma [121] and glioblastoma [122]. DYRK3 is required for influenza virus replication [123].…”
Section: Other Dyrks and Human Diseasementioning
confidence: 99%
“…The effects of NRBF2 knockdown and irradiation on cell invasion and migration capacity were investigated by transwell cell invasion/migration assays, as previously described 25 . Cells (2 × 10 5 in serum-free medium containing 1 mM glucose) were seeded into the upper chambers of a 24-well Transwell chamber (Corning, Corning, NY, USA) fitted with a 5 μm pore-size insert and treated with NRBF2 siRNA and/or radiation for 24 h. Next, the medium in the lower chamber was changed to medium containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%